The Climax of Globalisation: : the Endurance of Internationalisation - Sall, Ebrima (International Journal of African Higher Education, 2020)
This article examines the contradictory trends in globalisation and their impact on internationalisation in higher education. It argues that the rapid global spread of the COVID-19 pandemic, that has posed one of the most formidable challenges to globalisation and internationalisation, was made possible precisely because of the advanced stage of development that globalisation had reached. The lockdowns and near total restriction on international mobility, closure of schools and universities, and other effects and responses to the pandemic add to the restrictions on internationalisation imposed by conservative regimes in the North and the South. The article focuses on three issues: i) the contradictory trends in globalisation as relevant to internationalisation; ii) Trumpism and deepening neoliberal globalisation; and iii) networks and institutions in promoting internationalisation in the Global South. It argues that Trumpism and Brexit involve a renegotiation of the terms of engagement and attempts to reposition and re-assert the hegemony of certain players in the global economy. The article argues that, although certain aspects of internationalisation in higher education have become more difficult to preserve, it has deepened in other ways and taken new forms, thanks to the extensive use of new communications media and technologies. Internationalisation has not always been, and will not always be, ‘intentional’, but it can be harnessed to being about a more equitable form of globalisation.